2002
DOI: 10.1002/esp.357
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term changes in the plan shape of a sandy beach in response to sheltering by a nearshore mud bank, Cayenne, French Guiana

Abstract: Montjoly is a headland-bound embayed sandy beach in Cayenne, French Guiana, that shows long-term plan shape equilibrium in spite of periodic changes in accretion and erosion that alternately affect either end of the beach. These changes are caused by mud banks that move alongshore from the Amazon. The mechanisms involved in changes in the plan shape of the beach in response to the passage of one of these mud banks were monitored between 1997 and 2000 from airborne video imagery and field work. The beach longsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 8 publications
2
27
0
2
Order By: Relevance
“…In the beach transects close to the southernmost distributary of the Mekong River, the removal during the winter monsoon of mud deposited on the outer trough and platform during the rainy season reflects this annual cycle of sediment transport. A similar alternation of mud coverage and removal was reported from a headland-bounded mesotidal beach in French Guiana that receives an abundant supply of mud from the Amazon and Orinoco rivers (Anthony et al, 2002;Dolique, 2004, 2006). For the beach in French Guiana, however, the cycle was irregular, ranging from months to years, and did not correlate with the seasonal fluctuations of deepwater wave direction and height.…”
Section: Seasonal Variations Of Beach Morphology and Sedimentologysupporting
confidence: 53%
“…In the beach transects close to the southernmost distributary of the Mekong River, the removal during the winter monsoon of mud deposited on the outer trough and platform during the rainy season reflects this annual cycle of sediment transport. A similar alternation of mud coverage and removal was reported from a headland-bounded mesotidal beach in French Guiana that receives an abundant supply of mud from the Amazon and Orinoco rivers (Anthony et al, 2002;Dolique, 2004, 2006). For the beach in French Guiana, however, the cycle was irregular, ranging from months to years, and did not correlate with the seasonal fluctuations of deepwater wave direction and height.…”
Section: Seasonal Variations Of Beach Morphology and Sedimentologysupporting
confidence: 53%
“…These shifts have been associated with changing climatic conditions, for example, in a detailed study of Narrabeen Beach, New South Wales, Australia, Ranasinghe et al (2004), showed that variations during strong positive/negative Southern Oscillation Index phases (El Niño/La Niña) influenced beach rotation. Other variables also influence rotation, as shown by Anthony et al (2002) at Montjoly Beach, Cayenne, French Guiana, where patterns of nearshore mudbank migration induced rotation. Similarly, Thomas et al (2011b) linked beach diminution and migration, associated with spit collapse, to multi-century shoreline rotation within the current area of study.…”
Section: Introductionmentioning
confidence: 93%
“…Morphological responses of embayed beaches to storm and gale forcing have also been studied in the Northern [17][18][19] and Southern Hemispheres by amongst others [10,14]. The underlying causes of wave directional change have also been linked to subtidal mud bank and sandbank migration [20][21][22]. Unlike the macrotidal beach work carried out in this research, most rotation studies utilize variations in the location or volume of the subaerial zone to identify shoreline response; this was because almost all were studied in locations with microtidal or mesotidal ranges see for example [10,20,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%